دور استيعاب الجملة الاسمية في تنمية مهارة الكتابة باللغة العربية بوصفها لغة ثانية - أتروك، محمد فارق هيمال (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
The aim of this research is to study the role of the nominal sentence comprehension in developing writing skill in Arabic as a Second Language (ASL) for students of level 4 in Quranic Language (Arabic Language) Division at Centre for Languages and Pre-University Academic Development (CELPAD) International Islamic University Malaysia. The research focuses on the role of the nominal sentence comprehension in developing writing skill in Arabic in general, structuring nominal sentences in Arabic, and making grammatical errors in writing in Arabic. The researcher used the quasi-experimental design where data were collected through the pre-test and post-test from 34 students in two groups, treatment and control. The results of the study indicated that there is a statistically significant difference between two groups, treatment and control, in developing writing skill in Arabic in general, structuring nominal sentences in Arabic, and making grammatical errors in writing in Arabic. The post-test scores for the treatment group that represent the nominal sentence comprehension were higher than the control group that represent the traditional teaching Arabic Language. In other words, there is a significant difference found in the nominal sentence comprehension approach in developing writing skill in ASL.